Challenges In Managing Records For Effective Service Delivery In Agricultural Firm A Case Of Kenya Agricultural And Livestock Research Organization (KALRO) Headquarters, Nairobi. - Benta, Ndenga Atieno; Kurgat, Kibiwott; Ndiku, Mbenge T. (Advances in Social Sciences Research Journal, 2019)
Records are important sources of both information and knowledge, they ensure that an organization makes timely, accurate, relevant and informed decisions. Therefore, records should be maintained and enhanced throughout their life by establishing appropriate records management programs. Effective and efficient service delivery to the Kenyan public still remains an issue of great concern. This is due to the slow, inefficient and deliberate or uninformed delivery of service to the public. It was the impetus of the study to identify the challenges experienced in managing records for effective service delivery at KALRO. Government institutions face various challenges with regard to the management of records. African countries have tried to undertake civil service reforms, but they have not been successful as anticipated. The study adopted both quantitative and qualitative research design. The population which was studied includes managers of various departments, registry staff, records managers, and staff in every relevant department or division at the headquarters of KALRO in Nairobi. Purposive sampling was used for the study. The finding of the study reveals that respondents disagreed that there was poor working conditions (M=1.89; SD=.762); files retention by action officers (M=1.59; SD=.591) and about Others( mix up of current , semi-current and noncurrent records in the registry) (M=1.90; SD=.549). On the hand the respondents strongly disagreed that there was lack of adequate facilities and equipment (M=1.23; SD=.421), users do not understand roles and importance of the registries (1.43; SD=.591), registry staff lack adequate training (M=1.18; SD=.382) and lack of proper implementation of records management policy (M=1.30; SD=.680). The study concluded that there was a positive relationship between record management practices and service delivery (r=.967; p value < 0.05). Best record management practices will enhance service deliver and improve efficiency and effectiveness in storage and accessing of information at any time it is required by any user. The study recommended that in order for the records management staff to update and improve their skills there was need for the organizations to identify and develop programs in records management in form of short-term courses, workshops and advanced education for those without records and archives knowledge.